Gene therapy in neuromuscular disorders - Rodrigo Holanda Mendonça; Edmar Zanoteli (Arquivos de Neuro-Psiquiatria)
Abstract Monogenic neuromuscular disorders are potentially treatable through gene therapy. Using viral vectors, a therapeutic transgene aims to restore normal levels of a protein not produced by the defective gene, or to silence a gene whose expression leads to toxic effects. Spinal Muscular Atrophy (SMA) is a good example of a monogenic disease that currently has an AAV9-based vector gene therapy as a therapeutic option. In this review, we intend to discuss the viral vectors and their mechanisms of action, in addition to reviewing the clinical trials that supported the approval of gene therapy (AVXS-101) for SMA as well as neuromuscular diseases that are potentially treatable with gene replacement therapy.